2022
DOI: 10.3389/fsurg.2022.871685
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Acute Cholecystitis Management: A Systematic Review of Current Literature

Abstract: IntroductionSince the beginning of the COVID-19 pandemic, many patients with clinically acute presentations have been approached differently. The fear of viral transmission along with the short period of study made patients delay their hospital visits and doctors reassess the approach of certain acute situations. This study aimed to assess the changes in the management of patients with acute cholecystitis before and during COVID-19.MethodsA systematic review of the literature using PubMed (MEDLINE), Scopus, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…In Period II, the PTGBD rate was significantly higher, successful conservative therapy showed a significantly lower rate, and there was no significant change in the surgery rate. A systematic review yielded comparable findings; however, the study reported that while the PTGBD rate was higher during the COVID period, there was also a higher rate of conservative therapy and a decrease in the rate of surgical treatment 11 . A recent article from July 2023 found similar results by examining data from US Academic Centers (comparing 15–15 months pre-pandemic and pandemic periods) 12 .…”
Section: Discussionmentioning
confidence: 86%
“…In Period II, the PTGBD rate was significantly higher, successful conservative therapy showed a significantly lower rate, and there was no significant change in the surgery rate. A systematic review yielded comparable findings; however, the study reported that while the PTGBD rate was higher during the COVID period, there was also a higher rate of conservative therapy and a decrease in the rate of surgical treatment 11 . A recent article from July 2023 found similar results by examining data from US Academic Centers (comparing 15–15 months pre-pandemic and pandemic periods) 12 .…”
Section: Discussionmentioning
confidence: 86%
“…Морфологічно розрізняють катаральні, флегмонозні та гангренозні форми. Існують ускладнені форми, які включають в себе: водянку, емпієму жовчного міхура, біліарні панкреатити, холангіти, перивезикальні абсцеси, інфільтрати, абсцеси печінки, перфорації жовчного міхура та жовчні перитоніти [9]. Згідно з Токійським гайдлайном 2018 р. розрізнять три ступені важкості гострого холециститу.…”
Section: вступunclassified
“…During the COVID-19 pandemic, medical organizations such as the Society of American Gastrointestinal and Endoscopic Surgeons and the European Association for Endoscopic Surgery have suggested that an alternative approach to surgery, i.e., antibiotic therapy, PC, and watch-wait, should be preferred in as cases where possible (3). The onset of the pandemic was difficult in many aspects.…”
Section: Introductionmentioning
confidence: 99%